Respuesta :
The original length is x
The new length = 8 1/6 feet = 49/6 feet
The difference between two lengths is 5/6 feet
x - 49/6 = 5/6
x = 5/6 + 49/6 = 54/6 = 9 feet
The original length of the rope is 9 feet
The new length = 8 1/6 feet = 49/6 feet
The difference between two lengths is 5/6 feet
x - 49/6 = 5/6
x = 5/6 + 49/6 = 54/6 = 9 feet
The original length of the rope is 9 feet
Answer: The original length of the rope is 9 feet.
Step-by-step explanation:
Here, x represents the original length of the rope,
And, the new length of the rope = [tex]8\frac{1}{6}=\frac{49}{6}[/tex] feet,
The difference between the new length and the old length of the rope
[tex]=x-\frac{49}{6}[/tex]
According to the question,
[tex]x-\frac{49}{6}=\frac{5}{6}[/tex]
[tex]x=\frac{5}{6}+\frac{49}{6}[/tex]
[tex]x=\frac{5+49}{6}=\frac{54}{6}=9[/tex]
Hence, The original length of the rope is 9 feet.